2017
DOI: 10.1177/0022487117705096
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Video-Based Professional Development: An Exploratory Experiment Intended to Identify Effective Features

Abstract: Although video cases and video clubs have become popular forms of teacher professional development, there have been few systematic investigations of designs for such programs. Programs may vary according to (a) whether teachers watch videos of their own/their peers’ instruction, or whether teachers watch stock video of unknown teachers; and (b) whether discussions are led by trained facilitators or by participants themselves. Using a factorial design, we defined four treatment conditions based on these possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 45 publications
0
45
0
4
Order By: Relevance
“…Some researchers were explicit about whether the video was self-created or a stock video (e.g. Beisiegel et al, 2018), others included details about video length (e.g. Jilk, 2016), and some included reference to whether videos were edited or unedited (e.g.…”
Section: Considerations For the Fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…Some researchers were explicit about whether the video was self-created or a stock video (e.g. Beisiegel et al, 2018), others included details about video length (e.g. Jilk, 2016), and some included reference to whether videos were edited or unedited (e.g.…”
Section: Considerations For the Fieldmentioning
confidence: 99%
“…As an example, Taylor et al (2016) implemented videocases for science teacher professional development and found a positive effect on their analysis of practice. Across disciplines, video is often used as a representation of practice (Grossman et al, 2014) to provide teachers opportunity to view classroom happenings either from their own classrooms or from the classroom of others (Beisiegel, Mitchell, & Hill, 2018). Various types of video have been employed to support teachers in a number of ways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Educational innovation includes the transformation of students into active agents through the use of ICTs (Chiecher & Melgar, 2018;Kang & Es, 2019). Advances in technology facilitate the creation of school activities focused on students (Beisiegel, Mitchell, & Hill, 2018). In particular, digital tools allow the communication, use and dissemination of information on the Internet (Ramírez Mera & Barragán López, 2018).…”
Section: Introductionmentioning
confidence: 99%